National aspire career fair 2023 (ASPIRE'23) - Nurul Ain Sabirah Abd Rahim, (Penerbit Universiti Kebangsaan Malaysia, 2024)
ASPIRE'23 is a career fair that allows the community to find a job to continue their career in the field they are in or are interested in pursuing a career in. With the theme of "Pathways to Success: Navigating Your Future," it is clear that this program will take participants on a new journey and guide them through the various paths and opportunities that lead to career success. Since it is difficult for someone to go to numerous places to find a job, this program allows participants to check out and have direct interviews with as many companies that are participating and interested in the career fair. Direct interviews are highly effective as they promptly determine whether candidates will advance to the next stage or secure the job, with results announced swiftly. Three thousand one hundred forty-one attendees participated in ASPIRE'23, including recent graduates, job seekers, individuals looking to advance their careers, and final-year students who are looking for industry training opportunities. As a result of the visitors' value, 2,496 interviews were conducted, leading to 215 attendees successfully finding a job, while 1,194 advanced to a second interview. ASPIRE'23 has the potential to improve graduate employability (GE), which is expected to increase from 90.2% in 2022 to 95% in 2023 while reducing the country's unemployment rate.